Masseter muscle defined sarcopenia and survival in head and neck cancer patients. Issue 4 (May 2022) - McGoldrick, David M.; Yassin Alsabbagh, Aghiad; Shaikh, Moinuddin; Pettit, Laura; Bhatia, Sunil K.
Abstract: Sarcopenia is increasingly recognised as a poor prognostic factor in older patients undergoing cancer treatment. Recently, masseter muscle cross sectional area (MMCSA) has been shown to accurately identify sarcopenic patients. We aimed to apply this novel technique to a head and neck cohort to identify any potential relationship with survival. A retrospective review was undertaken of patients over 65 years, diagnosed with squamous cell carcinoma of the head and neck and treated with curative intent in our unit between October 2009 and October 2017. MMCSA was measured on staging CT scans using a validated technique. Patients were categorised into tertiles and also high and low MMCSA groups based on gender based tertile and mean MMCSA values. Survival analysis was performed using the Kaplan-Meier and Cox regression methods. A total of 111 patients were included in the study. The average age was 74 years (range 65-92 years) and 69% were male. The majority of patients had malignancies of the oral cavity (41%) or larynx (37%). The overall survival was 46% with a follow-up between 24 and 60 months. MMCSA was significantly associated with worse overall survival when defined using a gender based mean cut-off point (p=0.038) or tertile groupings (p=0.026), but did not maintain significance in multivariable analysis. Masseter muscle defined sarcopenia was associated with worse survival in our cohort in univariate analysis. Opportunistic measurement of this new factor on staging scans may aid prognostication and management in older patients.